Synchronous adenocarcinoma and neuroendocrine carcinoma of the colon: a case report - Mohapatra, Sonmoon (J Surg Case Rep, 2016)
Neuroendocrine tumors (NETs) originating from the gastrointestinal tract are considered to be relatively rare tumors with a poor prognosis. We describe a case of an 83-year-old male who presented with complains of bleeding per rectum. Colonoscopy revealed two ulceroproliferative tumors, one in the sigmoid colon and another in the descending colon. The patient underwent left hemicolectomy. Based on the immunohistochemistry, the sigmoid colon tumor was diagnosed as well-differentiated adenocarcinoma, whereas the descending colon tumor was diagnosed as NET. NET coexisted with adenocarcinoma occurring separately in the same segment of colon, as in the present case, is distinctly rare and has not been reported earlier. The coexistence of the NETs with other primary malignancies has been increasingly recognized. Therefore, we recommend that the patients with the diagnosis of NETs should undergo further screening for the associated primary malignancies to prevent late-stage diagnosis of synchronous malignancies.